2016
DOI: 10.5964/ejop.v12i3.1118
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive distortions, humor styles, and depression

Abstract: Cognitive distortions are negative biases in thinking that are theorized to represent vulnerability factors for depression and dysphoria. Despite the emphasis placed on cognitive distortions in the context of cognitive behavioural theory and practice, a paucity of research has examined the mechanisms through which they impact depressive symptomatology. Both adaptive and maladaptive styles of humor represent coping strategies that may mediate the relation between cognitive distortions and depressive symptoms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 23 publications
(27 reference statements)
2
51
0
6
Order By: Relevance
“…In view of experimental findings that depressed individuals display negative interpretation biases and difficulties in applying emotion regulation strategies that involve processing mood-incongruent information (see Joormann & D'Avanzato, 2010), one could expect rather opposite results. Furthermore, nonclinical studies clearly demonstrate that people with increased depressive symptoms habitually use rather negative (maladaptive) than positive (adaptive) components of humor (Kuiper, Grimshaw, Leite, & Kirsh, 2004;Martin, 2007;Rnic et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In view of experimental findings that depressed individuals display negative interpretation biases and difficulties in applying emotion regulation strategies that involve processing mood-incongruent information (see Joormann & D'Avanzato, 2010), one could expect rather opposite results. Furthermore, nonclinical studies clearly demonstrate that people with increased depressive symptoms habitually use rather negative (maladaptive) than positive (adaptive) components of humor (Kuiper, Grimshaw, Leite, & Kirsh, 2004;Martin, 2007;Rnic et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, a positive relationship between self-progressive humor and empathy was found while a negative relationship was found between aggressive humor and empathy [49]. In a study investigating the relationship between humor types and cognitive distortion and depression [50], it was determined that the cognitive distortion and depression levels are lower in those who use the participatory and self-progressive humor; however, they are at a higher level in those using the aggressive and self-annihilatory humor. In another study that supports these findings [51], negative significant relationships were found in the pathological personality characteristics in DSM-5 and the positive humor types while positive significant relationships were found with the negative humor types.…”
Section: Literature Reviewmentioning
confidence: 93%
“…For example, Rnic et al (2016: 358) concluded that "The use of Self-Defeating humor may reinforce the individual's negative self-concept (thereby increasing negative affect), especially when others appear to agree with the individual's humorous actions or statements, or to react to their use of humor in a rejecting manner." Consequently, some authors advised to identify and decrease the use of self-defeating humor as a maladaptive behavior (e.g., Maiolino and Kuiper 2014;Rnic et al 2016). These conclusions rest on the assumption that the SD scale actually captures self-defeating humor and that engaging in this self-defeating humor causes or adds to the maladaptive outcomes and reduces well-being, either directly or by negative social reinforcements and consequences.…”
Section: Self-defeating Humormentioning
confidence: 99%
“…In line with the conceptualization of the selfdefeating humor style, empirical findings with the SD scale supported its relationships with lower well-being. For example, the SD scale was found to correlate negatively with psychological well-being (lower trait positive affect and global self-esteem and more trait negative affect; e.g., Kuiper 2014; Maiolino and Kuiper 2014;Martin et al 2003;Rnic et al 2016;Ruch and Heintz 2013;Ruch and Heintz 2017) and with maladaptive outcomes for others, such as hostility and antagonism (e.g., Martin et al 2003;Zeigler-Hill et al 2016).…”
Section: Introductionmentioning
confidence: 99%